PARŞÖMEN ESERLERİN TRİCHOPHYTON VERRUCOSUM'UN BULAŞMA KAYNAĞI OLABİLECEĞİNİN GÖSTERİLMESİ - YÜCEL, Ayhan; KANTARCIOĞLU, A. Serda (Cerrahpaşa Medical Journal, 2014)
Background and Observation. The dermatophytes are a group of fungi comprising three genera, Microsporum, Trichophyton and Epidermophyton which cause the disease tinea or ringworm in its various forms. Apart from M. gypseum, which exists normally in the soil, the natural habitat of the dermatophytes is the skin of warmblooded animals. In ancient times calve, sheep; goat.. skins have been used for the manufacture of parchment as a writing material. Trichophyton verrucosum was isolated from a parchment manuscript dated on XIVth century as the mycological deterioration agent of the material and the object was fumigated successively in a thymol chamber. Trichophyton species cause dermatophytoses infecting the keratinized tissues such as hair, nails; skin etc. of human and lower animals. T. verrucosum is a zoophilic pathogen usually contracted from cattle and this fungus mar survive for many years on dead materials in nature. Although certain animal skins were reported as the source of acquisition of dermotophytosis, the transmission possibility from a museum object to human has been demonstrated as the first time in research. This conclusion should be epidemiologically important as being demonstrated a possible contamination source of Trichophyton verrucosum.